KULTUR ANTI KORUPSI PADA REMAJA ,DAN MENANAMKAN NILAI-NILAI ANTI KORUPSI PADA SANTRI PONDOK PESANTREN SALAFIYAH DAWUHAN SITUBONDO - Siti Seituni; Irma Noervadila; Firman Jaya; Arico Ayani; Ahmad Hafas Rasyidi (STKIP PGRI SITUBONDO, 2022)
The prevalence of corruption in Indonesia is alleged to have occurred in all fields and sectors of development, while Islamic boarding schools are dormitories where students study together under the auspices of kyai and nyai mothers, as well as ustadz and clerics who teach many traditional religious sciences, by instilling an attitude of Tawadhu'. From here, the good character of the nation's successor can be cultivated into an Islamic person and has a high sense of Nationalism and follows the rules of Religion and the State. In accordance with the purpose of the Islamic Boarding School, which is an educational institution that aims to form students to become independent and have good morals. By applying the habit of being honest, responsible, disciplined both for oneself and the environment with the assessment method, group discussion forums, pre-tests, lectures and questions and answers, where the results of this service are santri as centers of service to print the character of the nation's successors without corruption, as well as a center for disseminating very significant anti-corruption values.